1975
DOI: 10.1139/v75-326
|View full text |Cite
|
Sign up to set email alerts
|

The Photolysis of Matrix Isolated cis-Thionylimide. 2. The Identification and Infrared Spectra of trans-HNSO and NSO

Abstract: PETER 0. TCHIR and RICHARD D. SPRATLEY. Can. J. Chem. 53,2331Chem. 53, (1975.It is shown that the low energy (h > 3000 A) photolysis of cis-HNSO in an argon matrix leads to formation of trans-HNSO. Four i.r. absorptions are observed and assigned for trans-HNSO and an approximate partial force field is calculated using data from isotopic substitutions. A comparison is made of the i.r. spectra of cis-and trans-HNSO using the intramolecular hydrogen bond of the cis form as a basis for explanation of the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 2 publications
3
38
0
1
Order By: Relevance
“…1, 2 The two highest frequency modes of SNO were assigned to bands in the resulting infrared spectrum at 1523.0 cm −1 (ν 1 ) and 789.7 (ν 3 ) cm −1 , 1 while a band at 1195 cm −1 was assigned to the SO stretch of OSN. 2 The 1523.0 cm −1 band of SNO and 1195 cm The known spectroscopic data for SNO and OSN have been included in atmospheric models of the Venusian atmosphere, 8,9 but it has yet to be established where else these simple molecular radicals may arise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, 2 The two highest frequency modes of SNO were assigned to bands in the resulting infrared spectrum at 1523.0 cm −1 (ν 1 ) and 789.7 (ν 3 ) cm −1 , 1 while a band at 1195 cm −1 was assigned to the SO stretch of OSN. 2 The 1523.0 cm −1 band of SNO and 1195 cm The known spectroscopic data for SNO and OSN have been included in atmospheric models of the Venusian atmosphere, 8,9 but it has yet to be established where else these simple molecular radicals may arise.…”
Section: Introductionmentioning
confidence: 99%
“…2 The 1523.0 cm −1 band of SNO and 1195 cm The known spectroscopic data for SNO and OSN have been included in atmospheric models of the Venusian atmosphere, 8,9 but it has yet to be established where else these simple molecular radicals may arise. To this point in time, there exists little experimental data on the gas phase spectral features of SNO and OSN, the only experimentally observed [N, O, S] isomers.…”
Section: Introductionmentioning
confidence: 99%
“…13 18 A common theme of these studies is that SNO or NSO were observed as a decomposition product of other S, N, and O containing molecules. Early assignments of the stretching vibrational frequencies of SNO and NSO came from Tchir and Sprately, 13,14 where isomers of HSNO were formed in an argon matrix and subsequent UV irradiation yielded several vibrational absorption peaks. Some of these peaks were then attributed to either SNO or NSO, resulting in an assignment of the NO stretch and SNO bend vibrational frequencies of SNO 13 and the SO stretching frequency for NSO.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these peaks were then attributed to either SNO or NSO, resulting in an assignment of the NO stretch and SNO bend vibrational frequencies of SNO 13 and the SO stretching frequency for NSO. 14 It was later suggested that the initial assignments of SNO vibrational frequencies were better matched to the SN and NO stretches, rather than the NO stretch and SNO bend. 18 In addition, the SO stretching frequency for NSO had a larger than expected isotopic shift, 14,15 which called into question its identification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation